A comparison of the performance of Mexican boys and girls on Witkin’s cognitive tasks - Mebane, Donata; Johnson, Dale J. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
According to Witkin, sex differences in cognitive style vary with the type of culture and the role women play in that culture. One goal of our research was to explore whether in a highly sex-role differentiated society like Mexican society, boys have a more field independent cognitive style than girls. The second goal of this study was to explore the relationship between child-rearing practices for Mexican boys and girls, their daily experiences, and their cognitive styles. The Children’s Embedded Figure Test and the Draw-a-Person test along with a child-rearing and daily experience questionnaire were administered to 87 Mexican children. Mexican boys were found to be more field independent than Mexican girls, and American girls were also more field independent than Mexican girls. There was a relationship between the child-rearing methods used and field independence for boys but for girls, daily experience was more highly related to field independence.